Stability of Li2CO3 in cathode of lithium ion battery and its influence on electrochemical performance. Issue 23 (16th February 2016) - Bi, Yujing; Wang, Tao; Liu, Meng; Du, Rui; Yang, Wenchao; Liu, Zixuan; Peng, Zhe; Liu, Yang; Wang, Deyu; Sun, Xueliang
Abstract : Lithium carbonate is an unavoidable impurity at the cathode side. Abstract : Lithium carbonate is an unavoidable impurity at the cathode side. It can react with LiPF6 -based electrolyte and LiPF6 powder to produce LiF and CO2, although it presents excellent electrochemical inertness. Samples of Li2 CO3 -coated and LiF-coated LiNi0.8 Co0.1 Mn0.1 O2 were prepared to compare their influence on a cathode's behavior. After 200 cycles at 1C, in contrast to 37.1% of capacity retention for the Li2 CO3 -coated material, the LiF-coated LiNi0.8 Co0.1 Mn0.1 O2 retained 91.9% of its initial capacity, which is similar to the fresh sample. This demonstrates that decomposition of Li2 CO3 can seriously deteriorate cyclic stability if this occurs during working.